Intracranial volume (ICV) in isolated sagittal craniosynostosis measured by 3D photocephalometry: a new perspective on a controversial issue - Seeberger, Robin; Hoffmann, Jürgen; Freudlsperger, Christian; Berger, Moritz; Bodem, Jens; Horn, Dominik; Engel, Michael (Journal of cranio-maxillofacial surgery, 2016)
There are still controversies regarding the intracranial volumes in patients with isolated sagittal craniosynostosis compared to a healthy population. This study aimed to compare the intracranial volume of children with sagittal synostosis and scaphocephaly to an age- and gender-matched control cohort using three-dimensional (3D) photogrammetry.